2015
DOI: 10.1371/journal.pone.0139217
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Serum Vitamin D Concentrations and Allostatic Load as a Measure of Cumulative Biological Risk among the US Population: A Cross-Sectional Study

Abstract: IntroductionThe allostatic load (AL) index is a multi-systemic measure of physiologic dysregulation known to be associated with chronic exposure to stress and adverse health outcomes. We examined the relationship between AL and serum 25-hydroxyvitamin D (25(OH)D) concentration in non-institutionalized US adults.MethodsData from the Third National Health and Nutrition Examination Survey (NHANES III, 1988–94) were used to calculate two versions of AL including 9 biomarkers and another two with 14 biomarkers (sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 57 publications
0
33
1
Order By: Relevance
“…Vitamin D deficiency in plasma was found in the CG, which has been described to be inversely associated with physiological dysregulation associated with chronic exposure to stress and adverse health outcomes [104]. Deficiency of vitamin D has also been found to independently predict cognitive impairment [105]. Although previous studies have related alcohol consumption with lower levels of vitamin D in plasma, we found higher levels of this vitamin in AG [106][107][108].…”
Section: Discussioncontrasting
confidence: 47%
“…Vitamin D deficiency in plasma was found in the CG, which has been described to be inversely associated with physiological dysregulation associated with chronic exposure to stress and adverse health outcomes [104]. Deficiency of vitamin D has also been found to independently predict cognitive impairment [105]. Although previous studies have related alcohol consumption with lower levels of vitamin D in plasma, we found higher levels of this vitamin in AG [106][107][108].…”
Section: Discussioncontrasting
confidence: 47%
“…Of the 26 variables used in the 18 equations, 24 variables were continuous and two were categorical. The two categorical variables were asthma, present or absent and antibodies to herpes simplex virus I or II, present or absent[9,21]. Depending on the number of variables included in the ALS equation, scores ranged between 0 and 14.…”
Section: Perspectivementioning
confidence: 99%
“…al,’s analysis of NHANES data suggests a cross-sectional relationship between low vitamin D levels and higher biological risk, including AL. 26 Our own data suggest that adding vitamin D sufficiency to the AL index increases the strength of prediction for adverse perinatal outcomes. 27 In general, women who breastfeed are more likely to be supplementing their vitamin D intake (although supplementation also varies by SES), another possible contributor to breastfeeding’s protective effect.…”
Section: Discussionmentioning
confidence: 85%